Analysis of Procurement and Demand for Raw Materials of Dried Fish Making Business in Bengkulu City - Bambang Sumantri; Sriyoto Sriyoto; Melysa Nabilasari (AGRITROPICA : Journal of Agricultural Sciences, 2022)
This study is intended to analyze the source of fresh fish and the quantity of fresh fish used in the business of making dried fish in Bengkulu City and analyze what factors affect the quantity of demand for fresh fish in the business of making dried fish in Bengkulu City. This research was conducted from January to February 2022 in Bengkulu City, more precisely, Sumber Jaya Village, Kampung Melayu District. The research location was determined purposively, and 86 dried fish makers were selected using the census method. The data used are primary and secondary, and the data analysis used is qualitative and quantitative. Sources of raw materials in dried fish are divided into three: self-catch, buy, and self-catch and buy. The largest percentage of sources of raw materials is to buy, where the place to get the most comes from fishermen directly. The quantity of raw material used is 10,563 Kg per production process. The factors that partially affect the quantity of demand for fresh fish by dried fish makers are the price of ice and the dummy of the business scale at the 95% confidence level.